Quantification of the relative age effect in three indices of physical performance - Sandercock, G. R. H.; Taylor, M. J.; Voss, C.; Ogunleye, A. A.; Cohen, D. D.; Parry, D. A. (The Journal of Strength and Conditioning Research, 2013)
The relative age effect (RAE) describes the relationship between an individual's birth month and their level of attainment in sports. There is a clustering of birth dates just after the cutoff used for selection in age-grouped sports, and it is hypothesized that such relatively older sportspeople may enjoy maturational and physical advantages over their younger peers. There is, however, little empirical evidence of any such advantage. This study investigated whether schoolchildren's physical performance differed according to which quarter of the school year they were born in. Mass, stature, body mass index, cardiorespiratory fitness, strength, and power were measured in 10 to 16 year olds (n = 8,550, 53% male). We expressed test performance as age- and sex-specific z-scores based on reference data with age rounded down to the nearest whole year and also as units normalized for body mass. We then compared these values between yearly birth quarters. There were no significant main effects for differences in anthropometric measures in either sex. Girls born in the first quarter of the school year were significantly stronger than those born at other times when handgrip was expressed as a z-score. As z-scores, all measures were significantly higher in boys born in either the first or second yearly quarters. Relative to body mass, cardiorespiratory fitness was higher in boys born in the first quarter and power was higher in those born in the second quarter. The RAE does not appear to significantly affect girls' performance test scores when they are expressed as z-score or relative to body mass. Boys born in the first and second quarters of the year had a significant physical advantage over their relatively younger peers. These findings have practical bearing if coaches use fitness tests for talent identification and team selection. Categorizing test performance based on rounded down values of whole-year age may disadvantage children born later in the selection year. These relatively younger children may be less to gain selection for teams or training programmes.